Unverricht-Lundborg Disease: Tackling the Challenges of a Complex Clinical Picture - Ferreira dos Santos, Mafalda (2024)
Unverricht-Lundborg disease (ULD), also called progressive myoclonic epilepsy type 1, is characterized by stimulus-induced myoclonus and seizures without major progressive cognitive deficit, usually presenting during late childhood and early adolescence. It is an autosomal recessive disease, and, so far, only pathogenic variants in the gene encoding cystatin B (CSTB) have been described. We report the case of a 9-year-old boy who presented with generalized tonic-clonic seizures and developed paroxysmal myoclonic events over several years. The patient was started on antiseizure medication, but disease progression resulted in several changes to the therapeutic scheme, with highly variable clinical responses. The genetic study detected the pathogenic variant c.67-1G>C p.(?) in heterozygosity in the CSTB gene, after having identified the typical dodecameric expansion in the other allele, confirming the diagnosis of ULD.